Case study on how to shorten the product development cycle - Ng, Sheau Ming. (2008)
The main goal of this case study is to find opportunities to buy time for less than this cost. These opportunities appear throughout the development process. This case study emphasize on the time saving opportunities in the “fuzzy front end”, where it is least expensive to improve time to market.